Pengaruh Pengelolaan Wisata Situ Lengkong Panjalu Terhadap Perubahan Adaptasi Masyarakat Desa Panjalu Kecamatan Panjalu Kabupaten Ciamis - Agus Irpan Nurhidayat; Sri Mulyati; Anisaa Fauziyah; Delisa Lestari; Tia Setiawati; Yani Astuti (Universitas 45 Surabaya, 2024)
This research discusses the development of religious tourism in Situ Lengkong Panjalu, Ciamis Regency and its impact on the local community. Situ Lengkong Panjalu is a lake in Panjalu Village which is a pilgrimage destination because of its religious and historical stories. The local government is revitalizing infrastructure to increase tourist attraction. However, the development project caused significant economic changes for local merchants. Even though there has been an increase in income for motorcycle taxi drivers and traders who have shifted to tourist locations, negative impacts have also occurred such as decreased income and community involvement in development planning. This research aims to understand how society adapts to these changes and cope with the increase in visitor interest. With a good understanding of socio-economic adaptation, tourism management can be more sustainable and inclusive.